Project-based learning - Quinapallo-Quintana, Arnaldo Miguel; Baldeón-Zambrano, Alicia Ximena (International research journal of management, IT and social sciences, 2024)
In the degree in Pedagogy in Experimental Sciences at ULEAM Chone extension, the effectiveness of the project-based learning methodology has not been evaluated, so it is necessary to determine its uses and advantages at the university level. The objective of the study is to analyze project-based learning among students of the Pedagogy in Experimental Sciences career. It is developed through a mixed approach that integrates qualitative and quantitative data, the inductive method is used, and the study population is made up of students of the degree. The survey technique is used. The results demonstrate that PBL contributes to the development of research and problem-solving skills, collaboration and teamwork, the application of theoretical knowledge to practical situations, and the motivation and commitment of students, with a positive experience in its use.